Right To Restitution For Victims of Human Trafficking Criminal ACTS - Widi Purnomo; Bastianto Nugroho; Adies Kadir (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
The aim is to find out about the Judge's Considerations in Deciding on the Right to Restitution in Decision Number 738/Pid.Sus/2023/Pt Sby) according to Positive Law. The research method used in the research carried out is the Normative Juridical legal research method, also called normative legal research or doctrinal legal research. Results of the Surabaya High Court Decision Number 738/PID.SUS/2023/PT SBY The judge's consideration in granting restitution to the victim was in accordance with the law and justice for the victim.